Symptom improvement in a South Asian patient with Parkinson’s disease treated with immediate- and extended-release carbidopa–levodopa: a case report - Gail Reiner; Michael Skipworth (Journal of Medical Case Reports)
Abstract Background Little is reported in literature about Parkinson’s disease and treatment responses among South Asians. Case presentation Under the supervision of a movement disorders neurologist, an 85-year-old South Asian American man in hospice care was sufficiently regenerated from an adjustment of medications for Parkinson’s disease, such that he was able to shift from being immobile, unable to speak, or safely eat and drink fluids orally, to walking, eating, drinking fluids, and communicating again. His initial symptoms motivated him to seek neurological care in 2012, with his first consultation with a movement disorders neurologist occurring in 2023. After receiving specialty care and adjusting his carbidopa–levodopa from immediate release to a combination short- and long-acting formulation, Rytary, he was discharged from hospice to home health care. He progressed from being almost entirely nonverbal, bed-bound, and solely dependent on artificial nutrition to supportive home-based physical therapy, which facilitated his ability to regain sufficient strength for ambulation, eating and drinking orally, and he can once again use expressive language. Conclusion Immediate-release carbidopa–levodopa given three to four times daily remains the most common medication regimen for managing Parkinson’s disease symptoms of tremor and rigidity, with benefits noted in responsive patients for 2 to 3 hours. Extended release and combination formulations of carbidopa–levodopa that combine short- and long-acting medications in one capsule provide symptom relief for responsive patients for 4–6 hours and should be considered when the benefit from immediate-release carbidopa–levodopa is limited. Little has previously been published about the potential for variations in carbidopa–levodopa formulation responsiveness in South Asians, though it has been suggested that Western guidelines for managing “off” periods where carbidopa–levodopa is less effective, may not apply to other ethnicities (Bhidayasiri et al. in Expert Rev Neurother 15(11):1285–1297, 2015). As exemplified in this case, greater understanding of non-Caucasian races’ responses to carbidopa–levodopa, extended release, and their combination formulas is needed as is the benefit from subspecialty care within neurology, where the art of medication management is enhanced by experience in movement disorders and where objective tools such as the Movement Disorder Society-Unified Parkinson’s Disease Rating Scale can measure stability, decline, or improvement within each patient pertaining to their activities of daily living, cognitive and motor functions impacted by Parkinson’s disease, as well as monitoring for adverse reactions to medications used for Parkinson’s disease, such as dyskinesias.